2022
DOI: 10.1002/alz.063807
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐life burdensome interventions among Medicare fee‐for‐service beneficiaries with no dementia, non‐advanced dementia, and advanced dementia

Abstract: BackgroundOlder adults with dementia have difficulties communicating their treatment preferences and experience end‐of‐life burdensome interventions with discomfort and limited benefits. This study compared utilization of burdensome interventions during the last 90 days of life among Medicare fee‐for‐service (FFS) beneficiaries with no dementia, non‐advanced dementia, and advanced dementia.MethodThis study utilized data from 2000‐2016 Health and Retirement Study (HRS) linked with Medicare and Medicaid claims, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…2,25 Previous research documents end of life care differences by race and ethnicity, with less use of advance care planning, hospice services, and more use of inpatient admissions and life-sustaining treatments in the last 90 days of life among non-Hispanic Black and Hispanic compared to non-Hispanic White beneficiaries. 26,27 Dementia is a progressive disease that evolves over time, and the care needs of individuals with dementia change as the disease progresses. Medicare is the largest payer for healthcare services for individuals with dementia, and Medicare expenditures for care for these populations are high.…”
Section: Discussionmentioning
confidence: 99%
“…2,25 Previous research documents end of life care differences by race and ethnicity, with less use of advance care planning, hospice services, and more use of inpatient admissions and life-sustaining treatments in the last 90 days of life among non-Hispanic Black and Hispanic compared to non-Hispanic White beneficiaries. 26,27 Dementia is a progressive disease that evolves over time, and the care needs of individuals with dementia change as the disease progresses. Medicare is the largest payer for healthcare services for individuals with dementia, and Medicare expenditures for care for these populations are high.…”
Section: Discussionmentioning
confidence: 99%
“…One group of researchers found that Medicare beneficiaries with advanced dementia who lived in the community were 1.8 times as likely to receive life-sustaining treatments in the last three months of life, compared with individuals without dementia living in the community. 941 Individuals with frequent transitions between health care settings are more likely to have feeding tubes at the end of life, even though feeding tube placement does not prolong life or improve outcomes. 942 The odds of having a feeding tube inserted at the end of life vary across the country and are not explained by severity of illness, restrictions on the use of artificial hydration and nutrition, ethnicity or gender.…”
Section: Life-sustaining Interventions At the End Of Lifementioning
confidence: 99%
“…943 However, individuals with advanced dementia are significantly more likely to receive tube feeding in the last three months of life compared with those without dementia. 941…”
Section: Life-sustaining Interventions At the End Of Lifementioning
confidence: 99%
See 2 more Smart Citations